Design of stage and recording console - Nupe, Harvard (Universiti Malaysia Sarawak (UNIMAS), 2002)
The console is where the mixing and amplification of the signal from audio producing media is performed. The console is widely used in the production of quality audio, such as in in the recording studio and radio station.